2009
DOI: 10.1002/joc.1950
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of extreme precipitation in Poland in the period 1951–2006

Abstract: ABSTRACT:The study investigated spatial and temporal variability of extreme precipitation trend magnitudes and their directions. Daily precipitation from 48 synoptic stations in Poland for the period 1951-2006 were used. Five indices of precipitation extremes were chosen: the highest 5-day precipitation total, precipitation total from events ≥90 th and 95 th percentiles as well as number of days with precipitation ≥90 th and 95 th percentiles of daily precipitation amount. Trends in extreme precipitation indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 49 publications
(62 reference statements)
2
90
0
1
Order By: Relevance
“…1 Il s'agit dans ce travail d'analyser la tendance des six indices de pluies journalières. Cette méthode a été déjà utilisée par plusieurs auteurs (Maheras et al, 2008;Sahani et al, 2012;Ozer et al, 2007;Lupikasza, 2008;Martinez et al, 2007). Le test de Mann-Kendall permet de déceler l'existence d'une tendance globale au sein d'une série de données temporelles et a déjà été utilisé pour la détection de tendance dans les séries pluviométriques et tester leur significativité (Vannitsem et al, 1991;Norrant et Douguédroit, 2004;Maheras et al, 2008;Chaouche et al, 2010;Tramblay et al, 2013;Driouch et al, 2010).…”
Section: Zone D'étude Et Base De Donnéesunclassified
“…1 Il s'agit dans ce travail d'analyser la tendance des six indices de pluies journalières. Cette méthode a été déjà utilisée par plusieurs auteurs (Maheras et al, 2008;Sahani et al, 2012;Ozer et al, 2007;Lupikasza, 2008;Martinez et al, 2007). Le test de Mann-Kendall permet de déceler l'existence d'une tendance globale au sein d'une série de données temporelles et a déjà été utilisé pour la détection de tendance dans les séries pluviométriques et tester leur significativité (Vannitsem et al, 1991;Norrant et Douguédroit, 2004;Maheras et al, 2008;Chaouche et al, 2010;Tramblay et al, 2013;Driouch et al, 2010).…”
Section: Zone D'étude Et Base De Donnéesunclassified
“…Very few changes were detected at a number of stations in Poland during 1951-2006(Wibig 2008aŁupikasza 2010). Only the number of days with precipitation increased significantly.…”
Section: Precipitation Extremesmentioning
confidence: 99%
“…According to Equation (1), the minimum value of PCI1 is 8.3, which occurs when the same amount of precipitation falls in each month. Oliver [7] suggested that monthly rainfall heterogeneity could be divided into four categories according to the PCI1 values: uniform precipitation distribution (PCI1 < 10), moderate precipitation distribution (PCI1: 10-15), irregular precipitation distribution (PCI1: [15][16][17][18][19][20] and highly irregular precipitation distribution (PCI1 > 20). PCI2 has been used to study daily rainfall heterogeneity [8], based on the fact that the precipitation frequency can generally be described by a negative exponential distribution (Equation (2)).…”
Section: Precipitation Concentration Indices (Pci)mentioning
confidence: 99%
“…It is, therefore, difficult to determine the real trend of a time series. To access the stability characteristics of trends evaluated in this study, we determined the stability of extreme temperature and precipitation trends using the statistical significance of the trends tested by the M-K method, following the approach of Lupikasza [17] and Hidalgo-Muñoz et al [18]. In this method, trend stability was defined as follows:…”
Section: Stability Testmentioning
confidence: 99%